The belly philosophical: Melville, Nietzsche, and the ascetic ideal. Issue 10 (26th November 2019) - Marsoin, Édouard
ABSTRACT: This essay explores the philosophical quality of Melville's fiction through its affinities with Nietzsche's writings, following as a thread the Nietzschean notion of 'ascetic ideal', elaborated by Nietzsche in the Genealogy of Morality (1887) and commented upon by Deleuze in Nietzsche and Philosophy (1962). Reading Melville after Nietzsche after Deleuze, this essay uncovers how in Melville's fiction, as in Nietzsche's writings, ways of thinking are connected to ways of dieting, especially in Moby-Dick (1851) and Pierre (1852). This results in a common image of thought between the two authors: the belly philosophical, a critique of what thinking entails, and a reevaluation of the role of the body and its affects in the thinking process. Three great Melvillean characters, Ishmael, Ahab and Pierre, thus dramatise the way in which dietetic choices are intertwined with epistemological and philosophical postures.